Aortoduodenal fistula successfully treated with endovascular repair. Issue 2 (25th December 2020) - Fuchigami, Junya; Miyamoto, Kyohei; Shibata, Naoaki; Yonemitsu, Takafumi; Ueda, Kentaro; Kato, Seiya
Abstract: Aortoduodenal fistula is a rare cause of life‐threatening upper gastrointestinal bleeding. Accurate diagnosis is essential to initiate definitive treatment because endoscopic hemostasis, which is the usual initial intervention for upper gastrointestinal bleeding, may be ineffective. This case underscores timely intervention using endovascular treatment for achieving hemostasis in aortoduodenal fistula. Abstract : Aortoduodenal fistula is a rare cause of life‐threatening upper gastrointestinal bleeding. Accurate diagnosis is essential to initiate definitive treatment because endoscopic hemostasis, which is the usual initial intervention for upper gastrointestinal bleeding, may be ineffective. This case underscores timely intervention using endovascular treatment for achieving hemostasis in aortoduodenal fistula.